Wanted: a renaissance in thinking about water - David, S. (2009)
Economic development, population growth, climate change and shifts in the geopolitical balance of power are putting enormous pressure on the earth's water resources. Physical and economic water scarcity can be addressed through eight practical policy actions that contribute to the triple bottom line of food security, reducing poverty and sustaining productive ecosystems.